Translation, cross-cultural adaptation, validity, reliability and stability of the Dutch Injury - Psychological Readiness to Return to Sport (I-PRRS-NL) scale - Slagers, A. J.; Reininga, I. H. F.; Geertzen, J. H. B.; Zwerver, J.; van den Akker-Scheek, I. (Journal of Sports Sciences, 2019)
The Injury Psychological Readiness to Return to Sport (I-PRRS) scale measures the psychological readiness of injured athletes to resume sports participation. The aim of this study was to translate and culturally adapt the I-PRRS scale into Dutch (I-PRRS-NL) and assess its validity, reliability, and stability in patients after anterior cruciate ligament reconstruction (ACLR). The original I-PRRS was translated and culturally adapted from English into Dutch, and tested for clinimetric quality. To assess concurrent validity, 150 patients completed the I-PRRS-NL scale and five questionnaires measuring related constructs 3-16 months after ACLR. All predefined hypotheses regarding correlations between the I-PRRS-NL scale and these questionnaires were confirmed, indicating good concurrent validity. For test-retest reliability, 107 patients completed the I-PRRS-NL scale again two weeks later. The I-PRRS-NL scale showed good internal consistency (Cronbach`s alpha 0.94) and test-retest reliability (ICC 0.89). Standard error of measurement was 4.2 and smallest detectable change was 11.6. No systematic bias between test and retest was found. As the scale appears unstable at item level, only the total score should be used. Overall, the I-PRRS-NL scale showed sufficient validity and reliability to assess the psychological readiness to resume sports among Dutch-speaking patients after ACLR.